Destination image and choice intention of university student travellers to Mauritius - Phau, Ian; Shanka, Tekle; Dhayan, Neema (Emerald Group Publishing Limited, 2010)
Purpose – The purpose of this paper is to examine the influences of information sources, namely organic sources and induced sources, on perceived destination image and destination choice intention of university student travellers to Mauritius. Design/methodology/approach – Data were collected using a convenience sample in a large university in Western Australia. A self‐administered questionnaire was designed using established scales. In total, 388 usable responses were collected and analyzed using a variety of statistical techniques. Findings – The perceived attractiveness of Mauritius as a vacation destination is based on the fact that tourists picture the island as one which offers good value for money and cheap travel. Both information sources are found to have an influence on perceived destination image and destination choice intention. Perceived destination image is found to predict destination choice intention. Research limitations/implications – The sample is limited to potential tourists in Western Australia. Larger or national sample can be used for future studies. Qualitative methods could be explored in future. Practical implications – It is recommended that destination marketers should use multiple sources of information to target tourists. In particular, the internet seems to be the highest incidence of information source. Originality/value – The paper has redressed some deficits in the literature. Prior studies have not examined Mauritius as a tourist destination. Neither have Australians been studied as potential tourists. It has also tested the conceptual determinants of perceived destination image and destination choice intention and has proved that destination image is a multidimensional concept.